The first man - Camus, Albert, 1913-1960.; Hapgood, David; Penguin Books (London : Penguin Books, 1996)
Autobiographical novel translated from the author's final, unfinished manuscript, tells the story of Jacques Cormery, an Algerian boy whose poverty-stricken, fatherless life is offset by the beauty of his country and his loving relationship with his deaf-mute mother.
Adult
Keywords: Camus, Albert, -- 1913-1960 -- Fiction; Boys -- Fiction; Fatherless family -- Fiction; Family life -- Fiction; Algeria -- Fiction